The goose that Laid the golden Eggs (Usborne Pub Ltd; London)
Poor Tom and Elena can't believe their luck when their goose lays a golden egg, but what happens when one golden egg a day just isn't enough? This is the classic story retold with simple text and delightful illustrations. It is part of the Usborne English Language Learners programme, featuring books from the Usborne Reading Programme, with audio CDs in British and American English, downloadable worksheets and teacher's notes.